Consumer Behavior, Attitude and Perception Toward Modern Trade Stores in Rural Vietnam - Massoud Moslehpour; Van Kien Pham (Jurnal Administrasi Bisnis, 2013)
Modern trade stores have been very successful in Vietnamese retail industry, espe-cially in some big cities. However, the popularity of such stores is still lagging behindthe traditional stores. In regard with this issue, many studies have been done overtime, but very few have been focused on rural regions in emerging countries likeVietnam. Thus, this study aims at exploring the reasons why Vietnamese consumersin the remote area prefer to shop at traditional stores instead of modern stores. Fur-thermore, this study attempts to fill the gap between these two types of formats. Theresearch uses quantitative method with the aid of SPSS software to analyze the data.The results show that consumers in the remote areas are still not willing to quit theirtraditional shopping habits for a new choice of store based on the current situation.Therefore, it is not the right time for investors to expand their modern business intothe country’s rural areas.Keywords: Modern Trade Store, Traditional Store, Rural Vietnam, Retail Industry,Consumer Behavior, Store Attributes.